Pelatihan Balut Bidai terhadap Keterampilan pada Mahasiswa/I Keperawatan - Devi Listiana; Yulita Elvira Silviani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aimed to determine the effect of splint dressing training on the skills of nursing students at STIKES Tri Mandiri Sakti Bengkulu. The research method used in this study was pre-experimental with one group pre-test post-test design. The results of this study indicate that the skills before treatment and after treatment are -9.247 with a value of p = 0.000 (p-value <0.05). In conclusion, there is an effect of splint dressing training on nursing students' skills at STIKES Tri Mandiri Sakti Bengkulu. Keywords: Skills, Bidai Dressing Training